New insights into mesenchymal stem cells in inflammatory subtypes of asthma - Hou, Zheng-yan; Hao, Yu-qiu; Zhang, Lin; Li, Wei; Gao, Peng (Frontiers in Immunology, 2025)
Asthma is a heterogeneous disease characterized by chronic airway inflammation, heightened reactivity, and structural remodeling. The responses of different phenotypes to traditional corticosteroid therapy vary significantly, with steroid resistance in low T-helper type 2 asthma remaining an urgent clinical challenge. In recent years, mesenchymal stem cells (MSCs) and their exosomes—mesenchymal stem cell-derived extracellular vesicles (MSC-EVs)—have emerged as promising therapeutic agents due to their potent immunomodulatory properties. In this review, we systematically explain how MSCs and MSC-EVs inhibit airway inflammation in asthma through multi-target immunoregulation, highlight their therapeutic potential in steroid-resistant asthma, and outline the challenges and optimization strategies involved in clinical translation, thereby providing a theoretical foundation for the development of novel therapies.